Density, spin and isospin correlations in low-density two-component Fermi superfluid - Isayev, A.A.; Yang, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Finding the distinct features of the crossover from the regime of large overlapping Cooper pairs to the limit of non-overlapping pairs of fermions (Shafroth pairs) in multi-component Fermi systems remains a topical problem in a quantum many-body theory. Here this transition is studied by calculating the two-body density, spin and isospin correlation functions in dilute two-componentFermi superfluid, taking as an example an infinite system of rotons and neutrons (nuclear matter). It is shown that criterion of the crossover (Phys. Rev. Lett. 95, 090402 (2005)), formulated for ultracold fermionic atomic gases and consisting in the change of the sign of the density correlation function at low momentum transfer, fails to describe correctly the density-driven BEC–BCStransition at finite isospin asymmetry or finite temperature. As an unambiguous signature of theBEC–BCS transition, one can use the presence (BCS regime) or absence (BEC regime) of the singularity in the momentum distribution of the quasiparticle density of states.